Outcomes of inflatable penile prosthesis insertion using a neotunica allograft in neophalluses of patients on the bladder exstrophy–epispadias complex spectrum. Issue 5 (October 2020) - Harris, Kelly T.; Wu, Wayland J.; Manyevitch, Roni; Haney, Nora M.; Burnett, Arthur L.; Bivalacqua, Trinity J.; Gearhart, John P.
Summary: Background: Men born on the bladder exstrophy–epispadias complex (BEEC) spectrum may undergo neophallus reconstruction with a variety of free flaps, most commonly radial forearm. In order to achieve erectile function, a penile prosthesis may be inserted following neophallus construction. Objective: In this study, we sought to describe the perioperative and clinical outcomes of inflatable penile prosthesis (IPP) insertion into neophalluses of patients along the BEEC spectrum. Study design: Using a prospectively maintained institutional BEEC database, patients who had undergone both neophallus creation and IPP placement were identified for this study. Surgery was performed by two surgeons with expertise in IPP implantation. Operative details and postoperative outcomes and complications were collected with review of the medical record. Results: Overall, there were a total of 13 men who underwent neophallus reconstruction with subsequent IPP placement. Of these men, 76.9% (10/13) had experienced successful primary closure in childhood. One patient had corporal loss secondary to complete primary repair of exstrophy (CPRE) following a failed primary attempt. The average age at IPP placement was 23.2 years (SD ± 5.06). Mean OR time (n = 11) was 244.8 min (SD ± 46.2). 76.9% (10/13) of the cases used AlloDerm™ as a neotunica albuginea for support of the IPP. Three patients (23.1%) experienced complications all of which required revision surgery. Two of these complications were erosions in patients for whom AlloDerm™ was not used in the initial IPP placement. Discussion: The results of this study suggest that IPP placement in neophalluses of males on the BEEC spectrum have low perioperative and postoperative morbidity with successful outcomes. While the rate of complications is notably higher in this group compared to the native penis IPP literature, the use of AlloDerm™ or other allograft materials may help to narrow this gap. Conclusions: IPP placement in neophalluses of men on the BEEC spectrum is successful in the majority of cases. Complications may be reduced with the use of AlloDerm™ in initial placement.